Hydrochemistry of groundwater in a coastal region and its repercussion on quality, a case study—Thoothukudi district, Tamil Nadu, India - Singaraja, C.; Chidambaram, S.; Anandhan, P.; Prasanna, Mohan Viswanathan; Thivya, C.; Thilagavathi, R.; Sarathidasan, J. (Springer, 2014)
A hydrogeochemical study was conducted in Thoothukudi district situated in the southeast coast of Tamil Nadu, India to identify the influence of saltwater intrusion and suitability of groundwater for domestic and agricultural purposes. Scattered studies of this coastal region have reported signs of seawater intrusion, salt pan and industrial activity together with natural weathering process. To have a holistic picture of geochemical processes in the entire district, a total of 135 groundwater samples were collected and analyzed for major cations and anions. The geochemical parameters were compared with world and Indian standards and it was found that most samples are unsuitable for drinking purpose. The geochemical facies of the groundwater showed Na–Cl as the dominant water type indicating the saline nature of the groundwater. Chadda’s plots show that most of the samples fall in the Na–Cl type of water due to seawater intrusion. The samples were classified with parameters like sodium absorption ratio, residual sodium carbonate, total hardness, chloride, index to base exchange, electrical conductivity and facies to determine their suitability for irrigation purpose. It was inferred that the samples falling along the coast are not suitable for the irrigation purpose. The seawater-mixing percentage indicates that strong mixing was observed in the near shore and at the proximity of the salt pan. The permanent hardness was predominant in all the samples compared to the carbonate hardness reducing its domestic usability.